2021
DOI: 10.4314/ajcem.v22i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of Pseudomonas species: an important tool to combat antibiotic resistance for patient safety in Gombe, Nigeria

Abstract: Background: Pseudomonas species are responsible for different healthcare-associated infections and are inherently resistant to many commonly used antibiotics. Hospital antibiograms are either absent or not regularly available in most healthcare facilities in Nigeria. The objective of this study is to present the antibiogram of Pseudomonas isolates in Federal Teaching Hospital Gombe (FTHG) in order to guide antibiotic prescription for better patient safety in the hospital.Methodology: The is a hospital-based cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(11 reference statements)
1
1
2
Order By: Relevance
“…Gram negative bacteria E. coli, Klebsiella and Pseudomonas had low to moderate sensitivity to cephalosporins and the penicillin especially the first line antibiotics. This was similar to an earlier report from our centre [99]. Duru et al…”
Section: Discussionsupporting
confidence: 94%
“…Gram negative bacteria E. coli, Klebsiella and Pseudomonas had low to moderate sensitivity to cephalosporins and the penicillin especially the first line antibiotics. This was similar to an earlier report from our centre [99]. Duru et al…”
Section: Discussionsupporting
confidence: 94%
“…All the S. aureus isolates in our study were resistant to penicillin G, which is similar to the results reported by Andrianarivelo et al, (20) (24) in Morocco. Resistance rate of S. aureus to gentamicin was 20% in our study but lower rates were reported in different studies conducted in Madagascar with 5.67% (18), Burkina Faso with 0% (25), Uganda with 0% (26) and Morocco with 2.2% (24). The best anti-staphylococcal activities were exhibited by chloramphenicol (100% sensitivity), clindamycin (100% sensitivity) and fusidic acid (90% sensitivity), which was in concordance with results from studies conducted in Burkina Faso (25) and Madagascar (20).…”
Section: Antibiotic Profile Of Selected Mdr Bacteriacontrasting
confidence: 75%
“…A low resistance rate to imipenem was reported by Ettu et al, (15) in Nigeria, but Osundiya et al, (16) in Lagos reported high ceftazidime resistance rate of 79.4%, while ceftazidime resistance rate of 23.5% was reported by Kpoda et al, (17) in Burkina Faso. Our study report resistance rate of P. aeruginosa to ciprofloxacin of 33.3% but a higher rate (73.8%) was reported by Manga et al, (18) in Nigeria. Levofloxacin and amikacin had the best activity against P. aeruginosa isolates with sensitivity rate of 77.2% for each antibiotic in our study.…”
Section: Antibiotic Profile Of Selected Mdr Bacteriacontrasting
confidence: 53%
“…In clinical settings, obtaining an antibiogram before administering antibiotics can enable healthcare providers to select the most suitable antibiotic by identifying the specific bacteria causing the infection and their susceptibility to different antibiotics, ensuring optimal treatment outcomes. 12 Moreover, it aids in combating antibiotic resistance, 13 as tailoring treatment based on antibiogram results minimizes the risk of fostering antibiotic-resistant bacterial strains, which can mitigate the occurrence of associated adverse reactions and shorten hospital stays. 14 The Middle East faces a serious challenge with antibiotic resistance due to the high frequency of multidrug-resistant (MDR) infections, especially among Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%